Prevalensi bakteri Salmonella sp. pada daging ayam potong di pasar tradisional, pasar modern, dan merek terkenal di kota Medan. - Lulu Ilma Khoirun Nissa; Yayuk Putri Rahayu; D. Elysa Putri Mambang; Anny Sartika Daulay (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Chicken is a source of animal protein for humans. Chicken meat generally contains unsaturated fat; chicken meat also has a compact meat texture and simple protein, so it is easily digested. However, chicken meat can also be contaminated with Salmonella sp. Pathogenic bacteria can cause typhus or typhoid fever, caused by traders' lack of cleanliness and hygiene or their environment. Research was conducted to identify the presence of Salmonella sp. Pathogenic bacteria and analysing the value of Salmonella sp. Pathogenic bacteria contamination that met the Indonesian National Standard (SNI), namely harmful/25g in chicken meat from traditional markets, modern markets, and well-known brands in Medan City, and to determine the prevalence value of Salmonella sp. Bacteria. The method of research uses Total Plate Count (TPC). An identification test is first carried out to calculate and determine the presence of bacteria in a test sample for the existence of Salmonella sp. Pathogenic bacteria and choose the total value of contaminants using a Total Plate Count (TPC), then identify using a gram staining test. These biochemical tests include the indole test, MRVP test, citrate test, urea test, TSIA test, and LIA test. Then, the last one determines the Prevalence value of Salmonella sp. Bacteria. The results showed that the samples of traditional market and modern market chicken meat were positive for the presence of the pathogenic bacteria Salmonella sp. by obtaining Subgenus Salmonella Typhimurium on N2H8 sample code APTL and APTB, N3H15 sample code APTL, APTB, APMI and obtaining Subgenus Salmonella Thypi on N3H15 sample code APMS and the contamination value of the pathogenic bacteria Salmonella sp. Exceeds the threshold and does not meet the Indonesian National Standard (SNI), namely negative/25g. The prevalence value obtained by the pathogenic bacteria Salmonella sp. in broiler meat at Traditional Markets, Modern Markets, and well-known brands is 75%, 50%, and 0%, respectively.